Alternative Theories of Distribution - Kaldor, Nicholas (Review of Economic Studies, 1955)
Journal Article Alternative Theories of Distribution Get access Nicholas Kaldor Nicholas Kaldor Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 83–100, https://doi.org/10.2307/2296292 Published: 01 January 1955